2014
DOI: 10.1097/bot.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcar Screw Use in Surgical Neck Fractures of the Proximal Humerus With Unstable Medial Support

Abstract: In humeri with normal alignment, calcar screws can provide additional stability even when a medial deficiency exists. The use of calcar screws in humeri with varus deformity showed no biomechanical superiority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…The importance of reducing and maintaining the medial calcar to provide biomechanical support for a laterally placed plate has been recognized. Researchers concluded that medial support screws played a key role in PHILOS fixation of displaced PHF, but a biomechanical study showed the addition of medial support screws had no effect on the stiffness of the medial cortex in cases with varus malunion. In addition, a clinical study demonstrated that the place of calcar screws might lead to a high risk of humeral head necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of reducing and maintaining the medial calcar to provide biomechanical support for a laterally placed plate has been recognized. Researchers concluded that medial support screws played a key role in PHILOS fixation of displaced PHF, but a biomechanical study showed the addition of medial support screws had no effect on the stiffness of the medial cortex in cases with varus malunion. In addition, a clinical study demonstrated that the place of calcar screws might lead to a high risk of humeral head necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of medial support screws has been advocated in cases of medial comminution. 1,6,20,21 Furthermore, the augmentation of head screws to compensate for low BMD has been shown to increase failure loads and stiffness after locking plate fixation of proximal humeral fractures. 5,10,14,16 Significant reductions in the complication rate with augmentation have yet to be proven.…”
mentioning
confidence: 99%
“…Calcar screws play an important role in providing medial support [12, 21]. The current study showed that the calcar screws endured heavy loads from the medial column.…”
Section: Discussionmentioning
confidence: 69%